2013
DOI: 10.1186/1471-2180-13-188
|View full text |Cite
|
Sign up to set email alerts
|

Variability of antibiotic susceptibility and toxin production of Staphylococcus aureus strains isolated from skin, soft tissue, and bone related infections

Abstract: BackgroundStaphylococcus aureus is an opportunistic commensal bacterium that mostly colonizes the skin and soft tissues. The pathogenicity of S. aureus is due to both its ability to resist antibiotics, and the production of toxins. Here, we characterize a group of genes responsible for toxin production and antibiotic resistance of S. aureus strains isolated from skin, soft tissue, and bone related infections.ResultsA total of 136 S. aureus strains were collected from five different types of infection: furuncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
7
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 64 publications
(60 reference statements)
5
35
7
5
Order By: Relevance
“…However, high detection frequencies of eta (11.3%) and etb (9%) were reported in Sabouni study [29] and almost the same incidence was reported in other studies [6,30,31]. This may be sensible because none of the MRSA strains in the current survey was isolated from children with skin diseases including staphylococcal scalded skin syndrome (SSSS), impetigo, or blisters.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…However, high detection frequencies of eta (11.3%) and etb (9%) were reported in Sabouni study [29] and almost the same incidence was reported in other studies [6,30,31]. This may be sensible because none of the MRSA strains in the current survey was isolated from children with skin diseases including staphylococcal scalded skin syndrome (SSSS), impetigo, or blisters.…”
Section: Discussioncontrasting
confidence: 39%
“…In addition, several authors have reported that MRSA strains have become not only resistant to beta-lactam antibiotics, but they have also acquired additional resistance to non-betalactam antibiotics, especially aminoglycosides [9]. Moreover, the presence of resistance gene to methicillin may affect toxin production [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of PVL-producing strains does not exceed 2-5% among human routine clinical isolates in Europe, but can be higher in some other countries [111]. Associations with osteomyelitis and pyomyositis are now strongly suggested [117][118][119][120][121][122][123]. The locus encoding PVL is inside related bacteriophages [124][125][126][127]128].…”
Section: Panton-valentine Leukocidin (Pvl)mentioning
confidence: 96%
“…O Staphylococcus aureus tem ocupado lugar de destaque na etiologia das infecções hospitalares, entre outras, em função de sua alta versatilidade em adquirir resistência aos antimicrobianos (1,2,3) . A partir dos anos 40 do século XX, surgiram os primeiros registros de surtos por S. aureus resistentes à penicilina em ambiente hospitalar e nos anos 60 esta resistência se estendeu às penicilinas β-lactâmicas reconhecendo-se, então, no final daquela década, as cepas Staphylococcus aureus resistentes à meticilina (MRSA) como responsáveis por uma pandemia (1,2) .…”
Section: Introductionunclassified